Translation Of Rauf Parfi’s Poems Into French: Expression Of Poetic Meaning And Artistic Imagery (Zien Journal of Social Sciences and Humanities, 2025)
The period following Uzbekistan’s independence witnessed a creative renaissance among poets and writers, exemplified by figures such as Abdulla Oripov, Erkin Vohidov, Shavkat Rahmon, Muhammad Yusuf, Rauf Parfi, Usmon Azim, and Azim Suyun. Post-independence works introduced new thematic and stylistic interpretations of national identity, independence, and freedom. This study examines the translation of Rauf Parfi’s poetry into French by the skilled poet and translator Jean Pierre Balpe, focusing on the linguistic, stylistic, and poetic aspects. The analysis highlights the challenges of conveying both semantic meaning and poetic form, emphasizing the importance of linguistic and cultural competence for translators